Ciekawostki o przyszłym wieszczu zwerbalizowane w komentarzach Emilii Kiereś do "Ballad i romansów" Adama Mickiewicza = Curiosity about the future bard as expressed in commentaries by Emilia Kiereś based on "Ballads and Romances" by Adam Mickiewicz - Węgorowska, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of this discussion is to comment on the works of Adam Mickiewicz in his youthful years. The curiosity expressed in the ballads allows for a betterThese inspired Emilia Kieres to write her commentaries with a view to making it easier for contemporary readers to read and,thus, access Mickiewicz`s Ballads and Romances. understanding of the personality-characteristic predispositions of the author of the landmark works that initiated the Romantic trend in Polish literature.
Keywords: ciekawostka; komentarz; wieszcz; osobowościowo-charakterologiczna predyspozycja; werbalizacja; curiosity; commentaries; bard; personality-characteristic predisposition; verbalization